Suitability of β-lactoglobulin micro- and nanostructures for loading and release of bioactive compounds - Simões, Lívia S. (2022)
β-lactoglobulin (β-Lg) has the ability to form three-dimensional networks when heated above denaturation temperature (ca. 76 °C), since it undergoes conformational changes followed by subsequent protein-protein interactions, which allows designing stable micro- and nanostructures with affinity to bind to a wide range of molecules. In this sense, β-Lg micro (with particle size from 200 to 300 nm) and nano (with particle size ≤ 100 nm) structures were developed as a delivery system for the controlled release of hydrophilic and hydrophobic model compounds. Several concentrations of bioactive compounds were incorporated into β-Lg micro- and nanostructures and their association efficiency (AE) and loading capacity (LC) were determined. β-Lg structures were characterized in terms of structural properties, morphology, binding mechanisms, conformational changes and secondary structure. The impact of several conditions (e.g., pH, thermal processing, ionic strength and storage temperature) on the stability of β-Lg structures was also investigated. The release profile of bioactive compounds from β-Lg structures was determined in vitro using two food simulants with different hydrophobicities under different temperature conditions (at 4 °C and 25 °C). Data recorded showed that β-Lg nanostructures had the highest AE and LC comparing with β-Lg microstructures, for both bioactive compounds tested. β-Lg micro- and nanostructures with or without association of bioactive compounds showed to be stable under acidic (pH 2 to 3), neutral (pH 6) or alkaline (pH 10) conditions, thermal treatments up to 70 °C and during storage for 50 and 90 days at 25 °C and 4 °C, maintaining their particle size, PDI and surface charge (p > 0.05). The release kinetics of bioactive compounds from micro- and nanostructures fitted well the Linear Superimposition Model, being the relaxation the main release mechanism. Both compounds showed an initial burst effect followed by a slow release. All these findings provide new insights on which conditions the β-Lg micro- and nanostructures are more stable, and therefore more suitable to act as potential delivery systems for hydrophilic and hydrophobic bioactive compounds.